Environmental Impact from Drilling and Production of oil Activities: Sources and Recommended Solutions - Al-Haleem, Ayad; Awadh, Salih (Iraqi Journal of Science, 2023)
In petroleum industry, there are two major operations that can potentially impact the environment: Drilling and production. Both activities generate a significant volume of wastes include drill cuttings contaminated with hydrocarbons, wide variety of chemical additives, produced water and air pollutants. The potential impact depends primarily on the material, its concentration after release, and the biotic community that is exposed.In this study, many drilling locations and production facilities have been investigated and examined for their adverse effects on the environment. Contamination with hydrocarbons, heavy metals, salts, other associated wastes and air pollution were detected at many sits.Understanding of drilling and production wastes and how they are generated, improved operations that minimize or eliminate any environmental effects can be developed. Moreover, protection of human life, soil and water resources can be achieved through the implementation of proper waste management.